Structural characterisation on the nanoparticle doping of cerium (iv) oxide (ce02) into YBCO Superconductor / Afiq Awalludin - Awalludin, Afiq (Faculty of Applied Sciences, 2018)
This report present the study of structural characterization on the nanoparticle doping of Cerium (IV) Oxide (Ce02) into Yl-xCexBa2Cu30ɚ superconductor. The samples with varying value' of Ce (x = 0.00, 0.02, 0.05, 0.10 and 0.20) were prepared by using solid state method., The samples were characterized by using xray diffraction (XRD). The peak shifting, lattice parameter and its orthorhombicity were determined by using the data obtained from the XRD pattern. Pure sample (x = 0.00) was observed to have the highest value of lattice parameter a, c and highest unit cell volume which are 3.8491 A, 11.7385 A and 175.0778 A3 respectively. Meanwhile, the lattice parameter b of pure sample were in between of samples which have its x-value of 0.01 and 0.05. Generally, the trend of lattice parameter for a, c and its unit cell volume decreases as the x-value increases whereas the lattice parameter of b for each samples increases as the x-value increase. The XRD pattern shows that all samples exhibit orthorhombic structure and peak at 28 = 32° is shifted between [013] and [103] plane as the x-value increases.